Invisible higher education: Higher education institutions from Central and Eastern Europe in global rankings. (September 2017) - Boyadjieva, Pepka
The starting point of this study is the argument that not only rankings of higher education institutions (HEIs) are inescapable, but so is the constant criticism to which they are subjected. Against this background, the paper discusses how HEIs from Central and Eastern Europe countries (CEECs) are (non)represented in the main global university rankings. The analysis adopts two perspectives: 1) From the point of view of higher education in CEECs – what are the specificity, basic problems and perspectives of higher education in CEECs as seen through the prism of the global ranking systems? 2) From the point of view of the ranking systems – what strengths and weaknesses of the global ranking systems can be identified through the prism of higher education in CEECs? The study shows that most of the HEIs from CEECs remain invisible in the international and European academic world and tries to identify the main reasons for their (non)appearance in global rankings. It is argued that although global rankings are an important instrument for measuring and comparing the achievements of HEIs by certain indicators, they are only one of the mechanisms – and not a perfect one – for assessing the quality of higher education.